PERENCANAAN STRATEGIS PENDIDIKAN DALAM BUDAYA ORGANISASI SEKOLAH MENENGAH KEJURUAN - Dian Cita Sari; Sudirman Pekanbaru; Sriani Jambi (DIA: Jurnal Administrasi Publik, 2019)
In Vocational Education, analysis of the internal and external environment is a major step in the preparation of strategic planning. In general, strategic planning consists of three steps: strategy formulation, strategy implementation, and strategy evaluation. Strategy formulation includes developing a vision and mission, identifying external opportunities and threats to the organization, determining internal strengths and weaknesses of the organization, setting long-term goals, formulating alternative strategies, and choosing specific strategies to be implemented. The atmosphere and environment are critical components in the formulation of organizational goals, so that organizational improvement requires all relevant information towards achieving SMK quality. With a good organizational culture, organizations will develop far compared to organizations with weak culture. Analysis of the internal and external environment that integrates culture and the main task of this organization requires a learning process that includes the development of abilities in cultural transformation and transformation in SMK The research method used is a qualitative method with approach of feomenology. Research location in SMKN 2 Pekanbaru, Riau.